2023
DOI: 10.1007/s11356-023-25353-6
|View full text |Cite
|
Sign up to set email alerts
|

Disposal and resource utilization of waste masks: a review

Abstract: Waste masks pose a serious threat to the environment, including marine plastic pollution and soil pollution risks caused by landfills since the outbreak of COVID-19. Currently, numerous effective methods regarding disposal and resource utilization of waste masks have been reported, containing physical, thermochemical, and solvent-based technologies. As for physical technologies, the mechanical properties of the mask-based materials could be enhanced and the conductivity or antibacterial activity was endowed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 119 publications
2
5
0
Order By: Relevance
“…%. The data from Figure 11 indicated a discernible and consistent elevation in the softening point with increased fractions of SMR, a trend that aligns with outcomes previously chronicled in the literature [ 98 , 99 , 100 ]. Specifically, the softening point rose from 47.90 ± 0.11 °C for the pristine AP-5 binder to 57.85 ± 0.05 °C for the variant with 9 wt.…”
Section: Resultssupporting
confidence: 84%
“…%. The data from Figure 11 indicated a discernible and consistent elevation in the softening point with increased fractions of SMR, a trend that aligns with outcomes previously chronicled in the literature [ 98 , 99 , 100 ]. Specifically, the softening point rose from 47.90 ± 0.11 °C for the pristine AP-5 binder to 57.85 ± 0.05 °C for the variant with 9 wt.…”
Section: Resultssupporting
confidence: 84%
“…Several researchers have shown that the addition of mask fibers could improve the strength and endurance of asphalt, pavement, and even concrete. 8,9 As an alternative, sterilizing face masks for reuse through heating is proven to be effective in killing pathogens and results in minimal reduction in particle filtration efficiency (PFE). 10,11 However, even though this solution is environment-friendly, standardization and ethical concerns may be an issue.…”
Section: Inviting Environmental Awareness Through Small Sustainable A...mentioning
confidence: 99%
“…Currently, the most common methods for handling discarded masks include incineration and landfill disposal together with mixed discarded. 3,4 The incineration process inevitably generates fly ash and bottom ash, resulting in a significant release of CO 2 , which contradicts the global goals of achieving carbon peaking and carbon neutrality. 5 In addition, the significant influx of discarded masks containing plastic fibers into rivers and oceans has resulted in marine life, birds, and other animals being tangled in the plastic strings of the masks, which causes suffocation and eventual death.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a type of plastic, masks also possess pollution characteristics that are difficult to degrade. Currently, the most common methods for handling discarded masks include incineration and landfill disposal together with mixed discarded 3,4 . The incineration process inevitably generates fly ash and bottom ash, resulting in a significant release of CO 2 , which contradicts the global goals of achieving carbon peaking and carbon neutrality 5 .…”
Section: Introductionmentioning
confidence: 99%